Haemolytic complement activity in normal and duck-plague-virus-vaccinated ducks - BARMAN, N N; DAS, S K; SARMA, D K; SARMAH, A K; TALUKDAR, S K (The Indian Journal of Animal Sciences, 2013)
The haemolytic complement (C) level of the ducks of different age groups was estimated by using micro-complement fixation test (micro-CFT) and radial haemolytic assay (RHA) technique. In 15-day-old duckling the mean C titre was very low; however, in adult ducks the titre was significantly high. The C titre decreased from 60 hr post-challenged infection with the duck plague virus (DPV).